Seasonal Difference in Percutaneous Absorption of N, N‐Dimethylformamide as Determined Using Two Urinary Metabolites. Issue 4 (3rd October 2014) - Tsuda, Yoko; Miyauchi, Hiroyuki; Minozoe, Aoi; Tanaka, Shigeru; Arito, Heihachiro; Tsukahara, Teruomi; Nomiyama, Tetsuo
Abstract : Seasonal Difference in Percutaneous Absorption of N, N ‐Dimethylformamide as Determined Using Two Urinary Metabolites: Yoko TSUDA, et al . Department of Preventive Medicine and Public Health, Shinshu University School of Medicine— Objective: We evaluated the percutaneous absorption of N, N ‐dimethylformamide (DMF) in DMF‐exposed workers in the summer and winter by assessing their urinary levels of DMF metabolites. Methods: Breathing‐zone concentrations of DMF and workers' urinary levels of N ‐methylformamide (NMF) and N ‐acetyl‐ S ‐( N methylcarbamoyl)‐cysteine (AMCC) were simultaneously measured in the summer and winter in 193 male workers wearing a respirator and chemical protective gloves. Results: The mean breathing‐zone concentrations of DMF in both seasons were below the occupational exposure limit of 10 ppm. Although there was no significant seasonal difference in the breathing‐zone concentrations of DMF, workers' urinary levels of NMF and AMCC were significantly higher in the summer than in the winter. Log‐transformed urinary levels of the metabolites were significantly correlated with log‐transformed breathing‐zone concentrations of DMF in the summer, whereas no significant correlation between AMCC and DMF was found in the winter. The urinary levels of AMCC were dispersed more widely than those of NMF, suggesting that urinary AMCC reflected the cumulative exposure to DMF over a workweek. Conclusions: Percutaneous absorption was the principal route of exposure to DMF for the respirator‐wearing workers. Increased urinary levels of NMF and AMCC in the summer were attributed to increased percutaneous absorption of DMF resulting from the increased amount of water‐soluble DMF absorbed by sweaty skin caused by the increased summertime room temperature and humidity.